Biofilm community structure and the associated drag penalties of a groomed fouling release ship hull coating. Issue 2 (7th February 2018) - Hunsucker, Kelli Z.; Vora, Gary J.; Hunsucker, J. Travis; Gardner, Harrison; Leary, Dagmar H.; Kim, Seongwon; Lin, Baochuan; Swain, Geoffrey
Abstract: Grooming is a proactive method to keep a ship's hull free of fouling. This approach uses a frequent and gentle wiping of the hull surface to prevent the recruitment of fouling organisms. A study was designed to compare the community composition and the drag associated with biofilms formed on a groomed and ungroomed fouling release coating. The groomed biofilms were dominated by members of the Gammaproteobacteria and Alphaproteobacteria as well the diatoms Navicula, Gomphonemopsis, Cocconeis, and Amphora. Ungroomed biofilms were characterized by Phyllobacteriaceae, Xenococcaceae, Rhodobacteraceae, and the pennate diatoms Cyclophora, Cocconeis, and Amphora. The drag forces associated with a groomed biofilm (0.75 ± 0.09 N) were significantly less than the ungroomed biofilm (1.09 ± 0.06 N). Knowledge gained from this study has helped the design of additional testing which will improve grooming tool design, minimizing the growth of biofilms and thus lowering the frictional drag forces associated with groomed surfaces.